The Genome-Scale Integrated Networks in Microorganisms - Hao, Tong; Wu, Dan; Zhao, Lingxuan; Wang, Qian; Wang, Edwin; Sun, Jinsheng (Frontiers in Microbiology, 2018)
The genome-scale cellular network has become a necessary tool in the systematic analysis of microbes. In a cell, there are several layers (i.e., types) of the molecular networks, for example, metabolic network, transcriptional regulatory network and signal transduction network. It has been realized that the limitation and inaccuracy of the prediction exist just using only a single-layer network. Therefore, the integrated network constructed based on the networks of the three types attracts more interests. The function of a biological process in living cells is usually performed by the interaction of biological components. Therefore, it is necessary to integrate and analyze all the related components at the systems level for the comprehensively and correctly realizing the physiological function in living organisms. In this review, we discussed three representative genome-scale cellular networks: metabolic network, transcriptional regulatory network and signal transduction network, representing different levels (i.e., metabolism, gene regulation and cellular signaling) of a cell’s activities. Furthermore, we discussed the integration of the networks of the three types. With more understanding on the complexity of microbial cells, the development of integrated network has become an inevitable trend in analyzing genome-scale cellular networks of microorganisms.